Społeczne skutki alkoholizmu w latach 1970-1980 na przykładzie Bydgoszczy (Kronika Bydgoska, 2013)
In the period of the Polish People’s Republic, alcoholism was one of the main pathogenic reasons of the Polish society. It caused an increase in crime (including juvenile crime), family disintegration, and development of alcohol addiction. In the period of the communist dictatorship in Poland, there was a dramatic, compared to the inter-war period, an almost tenfold increase in consumption of alcoholic beverages, and customary alcohol drinking transformed into pathological alcoholism. In 1970, Polish people spent about 50 milliard złotys on alcohol, and in 1980 - over 195 milliard złotys! To the communists in power, profits in the order of a few milliards flowing into the state budget from the sale of alcohol were more important than the social effects of alcoholism. It was the easiest way of getting back the money paid earlier to the citizens in the form of wages and old age and disability pensions. The article analysing the problem of alcoholism in Bydgoszcz in the decade of the 1970’s presents also the most important social effects of this phenomenon, among others, crimes and offences, alcohol-related diseases, and so-called social sponging. The article includes also tables depicting the above-named issues.